1990
DOI: 10.1007/bf00016499
|View full text |Cite
|
Sign up to set email alerts
|

Classification and characterization of the rice ?-amylase multigene family

Abstract: To establish the size and organization of the rice alpha-amylase multigene family, we have isolated 30 alpha-amylase clones from three independent genomic libraries. Partial characterization of these clones indicates that they fall into 5 hybridization groups containing a total of 10 genes. Two clones belonging to the Group 3 hybridization class have more than one gene per cloned fragment. The nucleotide sequence of one clone from Group 1, lambda OSg2, was determined and compared to other known cereal alpha-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
1
6

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 48 publications
4
136
1
6
Order By: Relevance
“…Induction of a-amylase gene expression is controlled through the interaction of regulatory proteins with cis-acting elements in the promoters of the a-amylase genes. Nucleotide sequence comparisons of severa1 rice, barley, and wheat a-amylase genes revealed a highly conserved sequence element (TAACRRA) in the promoters of these genes (Huang et al, 1990b). (DNA sequence ambiguity code: R = A or G.) This element is required for GA induction of a-amylase gene expression, hence the name Gibberellic Acid Response Element or GARE box (Rogers et (Ranjhan et al, 1991), but no clone for this putative 10th meniber of the gene family has been isolated to date.…”
Section: The Ca Slgnal Stimulates Cereal Seedling Source Metabolismmentioning
confidence: 99%
“…Induction of a-amylase gene expression is controlled through the interaction of regulatory proteins with cis-acting elements in the promoters of the a-amylase genes. Nucleotide sequence comparisons of severa1 rice, barley, and wheat a-amylase genes revealed a highly conserved sequence element (TAACRRA) in the promoters of these genes (Huang et al, 1990b). (DNA sequence ambiguity code: R = A or G.) This element is required for GA induction of a-amylase gene expression, hence the name Gibberellic Acid Response Element or GARE box (Rogers et (Ranjhan et al, 1991), but no clone for this putative 10th meniber of the gene family has been isolated to date.…”
Section: The Ca Slgnal Stimulates Cereal Seedling Source Metabolismmentioning
confidence: 99%
“…GUS activity was hardly detected in the corresponding tissues of the negative control plants (data not shown). Consistent with the GUS activity levels, the promoter region contains several important elements, such as an amylase-box, CARE, GARE, GCN4-motif, ACGT motif and AACA motif, which are involved in seed-specific and normal embryo-specific expression [24,[28][29][30][31]39]. Quantitative GUS assays showed that the highest expression was in Functional analysis of a GhGlcAT1 promoter 180 npg the anthers, with relatively high expression in the stigmas and styles.…”
Section: Histochemical and Quantitative Analysis Of Gus Activitymentioning
confidence: 89%
“…Furthermore, regulatory elements with homology to those identified in other seed/endospermspecific genes were found in the pGhGlcAT1 region such as an amylase-box, E-box, CARE, GARE, GCN4-motif, ACGT motif and AACA motif ( Table 1). The amylase-box was required for high expression of the gene in the seeds [24], while the E-box was shown to be bound by bHLH (basic helix-loop-helix) transcription factors and to regulate the seed-specific expression of seed storage protein genes and the expression of genes involved in anthocyanin biosynthesis [25][26][27]. The CARE and GARE boxes were required during seed germination in Arabidopsis and rice [28,29].…”
Section: Sequence Characterization Of the Ghglcat1 Promoter Regionmentioning
confidence: 99%
“…Deletion of the regions containing these motifs reduces GAupregulated expression (Huttly, Phillips & Tregear, 1992). The rice RAmy 1A and Osamy-c genes have TRE-like motifs adjacent to their pyrimidine boxes (Huang et al, 1990 ;, and for Osamy-c, nuclear protein has been shown to bind to this region. Thus both the O2S and TRE motifs appear to be specific for the low-pI amylases, and to be involved in the GA-induction system.…”
Section: Transcriptional Regulationmentioning
confidence: 99%